THE INTENSITY OF BIOFILM FORMATION ON TITANIUM AND ZIRCONIA ABUTMENTS DURING TREATMENT WITH IMPLANT-SUPPORTED PROSTHESES - S.-R. R. Ghot; M.M. Ugrin; O.M. Fal; A.Ya. Baryliak; M.A. Panas (Ukrainian Medical Stomatological Academy, 2017)
Bacterial adhesion is directly related to the character of the surface structure. It is also known that the adhesion intensity of bacteria varies depending on the material but there are not many studies which compare the intensity of biofilm formation, its bacteria and the impact on soft tissues. The microflora around dental implants appears to be similar to that which found around natural teeth and, thus, microbial pathogens associated with periodontitis may also contribute to implant failures. The surface of supraosseous implant elements is essential for the dental plaque formation and studies of its properties would prevent the process of periimplantitis. For the experiment three types of titanium disks (mechanically polished, sandblasted and acid-etched and Titanium Nitride surface) and zirconium oxide discs were used. We studied the bacterial colony formation on these samples. Experiment showed different adhesion properties of the bacteria depending on the surface character of the experimental material. The aim is to assess the intensity of biofilm formation on titanium and zirconia surfaces in an experimental study. Materials and methods: nine patients participated in this study. A removable acrylic device was adapted on the upper jaw with the two discs on each side which were glued to the buccal aspect of device in the molar-premolar region. After 24 hours all discs were removed into a sterile test tube and processed for microbiological study to identify two bacterial colonies Streptococcus mitis and Streptococcus salivarius. Scanning with electron microscopy was processed to evaluate the area of clean surface and the surface covered with bacteria. Statistical evaluation was done with GraphPad InStat 3 program. Results: Microbiological study in vivo showed that all surfaces were covered with bacteria. However, some differences were observed in different experimental groups. Most colonies of Streptococcus mitis were formed on the sandblasted/acid-etched titanium surface before the mechanical cleaning and after. The most significant difference in colonization of Str. mitis was on the surface of zirconium oxide, which had the smallest amount of colonies before mechanical cleaning, and after the cleaning the fewest Str. mitis colonies were on the polished titanium surface. The greatest amount of Streptococcus salivarius colonies was observed on sandblasted/acid-etched titanium surface and the smallest - on zirconium. Relatively small difference in intensity of biofilm formation was seen amid sandblasted/acid-etched and Titanium Nitride surfaces. Conclusion: 1. The lowest adhesive properties of microorganisms were observed on the zirconium oxide surface (p <0.05) and mechanically polished surface of titanium (p <0.05). Therefore, it is recommended to use these materials for dental abutments.  2. Excessive presence of such bacteria as Str. mitis and Str. salivarius leads to pathogenic bacteria coaggregation, and thus the presence of these bacteria on the surfaces of the implants can cause periodontitis and subsequent loss of the implant. 3.SEM showed the lowest percentage of bacterial adhesion on mechanically polished titanium (8%) and zirconium oxide surface (12%).